Public Speaking Training in Developing the Communication Skill of PKK Community in Ngidam Muncar, Susukan, Semarang - Itasari, Andri Astuti; Hastuti, Nurnawati Hindra; Maria, Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service is entitled